Genetic components of Escherichia coli involved in its complex prey-predator interaction with Myxococcus xanthus - Zhang, Ning; Li, Tingyi; Pan, Hongwei; Wang, Yipeng; Li, Qi; Luan, Jia; He, Xuesong; Shi, Wenyuan; Li, Yuezhong; Wang, Chuandong; Zhang, Fengyu; Hu, Wei (Frontiers in Microbiology, 2023)
Myxococcus xanthus and Escherichia coli represent a well-studied microbial predator-prey pair frequently examined in laboratory settings. While significant progress has been made in comprehending the mechanisms governing M. xanthus predation, various aspects of the response and defensive mechanisms of E. coli as prey remain elusive. In this study, the E. coli MG1655 large-scale chromosome deletion library was screened, and a mutant designated as ME5012 was identified to possess significantly reduced susceptibility to predation by M. xanthus. Within the deleted region of ME5012 encompassing seven genes, the significance of dusB and fis genes in driving the observed phenotype became apparent. Specifically, the deletion of fis resulted in a notable reduction in flagellum production in E. coli, contributing to a certain level of resistance against predation by M. xanthus. Meanwhile, the removal of dusB in E. coli led to diminished inducibility of myxovirescin A production by M. xanthus, accompanied by a slight decrease in susceptibility to myxovirescin A. These findings shed light on the molecular mechanisms underlying the complex interaction between M. xanthus and E. coli in a predatory context.